GENERAL CHARACTERISTIC OF THE DISTRIBUTION OF ABUNDANCE AND BIOMASS OF THE BENTHIC FAUNA OF THE DAGESTAN COAST OF THE MIDDLE CASPIAN - A. A. Abdulmedzhidov; A. S. Abdusamadov; A. M. Dokhtukaeva; L. A. Dudurkhanova (Юг России: экология, развитие, 2014)
The work gives the general characteristics of the distribution of abundance and biomass of the benthic fauna of the Dagestan coast of the Middle Caspian.